The Influence of Organizational Culture and Work Motivation on Employee Performance at GMIM Siloam Sonder Hospital - Tenda, Lyra; Areros, William A.; Rumawas, Wehelmina (Productivity, 2025)
This research aims to explore the influence of organizational culture and work motivation on employee performance at RSU GMIM Siloam Sonder. Using quantitative methods and Partial Least Square (PLS) analysis. From the results of this research, it was found that the variables Organizational Culture and Work Motivation had a positive and significant partial and simultaneous effect on employee performance at RSU GMIM Siloam Sonder. These results indicate that it is necessary for management to develop programs that can support organizational culture and work motivation to create a healthier organizational environment